2022
DOI: 10.1093/ofid/ofac264
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning for Infectious Disease Fellows—A Needs Assessment

Abstract: Background Online resources and social media have become increasingly ubiquitous in medical education. Little is known about the need for educational resources aimed at Infectious Disease (ID) fellows. Methods We conducted an educational needs assessment through a survey that aimed to describe ID fellows’ current use of online and social media tools, assess the value of online learning, and identify the educational content pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Infographics were used to teach on the fly or during rounds in most cases, but other methods, such as inclusion in didactic materials, were described as well. Febrile has been noted in previous publications as a well-received multimedia project for ID learners [ 1 , 11 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infographics were used to teach on the fly or during rounds in most cases, but other methods, such as inclusion in didactic materials, were described as well. Febrile has been noted in previous publications as a well-received multimedia project for ID learners [ 1 , 11 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of US internal and emergency medicine residents showed that 60%–80% of trainees are using educational podcasts on a weekly or monthly basis, and more than a third of infectious diseases (ID) fellows are commonly using online resources like websites and podcasts at least once a week as complements to traditional teaching [ 9–11 ]. When asked what online-based resources they are most likely to use, 55% of ID fellows selected podcasts, a proportion that was exceeded only by access to online board questions (77%) [ 11 ]. Trainees have identified benefits such as ease of use, lower barrier to learning, an engaging format, broad content exposure, and the ability to foster connection to their peers and the larger professional community [ 11–13 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ID trainees are already frequently learning from digital resources and have expressed interest in additional online resources. 28,29 Responses from the 2020 American Society of Transplantation Education Needs Assessment Survey demonstrated that many in the transplant and TID community feel they would learn best from various digital modalities (including 31% selecting video broadcasts, 9% podcasts, 8% web apps, and 3% social media). 30,31 This manuscript highlights the structure, content, and lessons learned from the ongoing IDDI program, as well as how the program can align with current and future TID education efforts.…”
mentioning
confidence: 99%
“…Twitter and Instagram have been identified as being utilized in ID [ 8–10 ]. An educational needs assessment survey of 110 ID fellows found that 55% used Twitter at least weekly and found it valuable for learning, whereas Facebook and Instagram were seen as having almost no value for learning for 56% and 53% of those surveyed [ 12 ]. Although there are many possible benefits to utilizing social media in healthcare education and communication [ 13 ], detailed descriptions of SoMe adoption and utilization have not been well characterized among adult and pediatric ID programs.…”
mentioning
confidence: 99%